2020
DOI: 10.33182/ml.v17i5.694
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the reconstruction of personal networks through residential migration trajectories

Abstract: This article examines how residential trajectories influence the spatiality and composition of personal networks. Three mechanisms are considered: the addition of spatially close network members, the selection of spatially distant network members, and the substitution of spatially distant network members by spatially close ones. An ego-centred network analysis combined with sequence analysis of residential experiences is used to capture the personal networks and the residential trajectories of individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The determinants of inbound tourism are examined in several studies. Some authors identified the potential uncertainty sources affecting tourism development such as conflicts, political instability, security, and terrorism (Ghaderi et al, 2017;Saha & Yap, 2014;Saha et al, 2017;Ganjour et al 2020;Rebhun, 2021;Vorobeva & Dana, 2021). But the economists dealing with tourism mostly use market demand theory analysing the demand and spending (Demir et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The determinants of inbound tourism are examined in several studies. Some authors identified the potential uncertainty sources affecting tourism development such as conflicts, political instability, security, and terrorism (Ghaderi et al, 2017;Saha & Yap, 2014;Saha et al, 2017;Ganjour et al 2020;Rebhun, 2021;Vorobeva & Dana, 2021). But the economists dealing with tourism mostly use market demand theory analysing the demand and spending (Demir et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%